2014
DOI: 10.4161/cbt.29187
|View full text |Cite
|
Sign up to set email alerts
|

Dual VEGF/VEGFR inhibition in advanced solid malignancies

Abstract: Our prior phase I study of the combination of vascular endothelial growth factor (VEGF) antibody, bevacizumab, and VEGF receptor (VEGFR) inhibitor, sunitinib, in advanced solid tumors identified an encouraging response evaluation. An expansion phase of this study was thus undertaken to obtain further safety data, response assessment and characterization of pharmacodynamic biomarkers in melanoma, renal, and adrenal carcinoma patients. Patients with metastatic solid tumors received sunitinib (37.5 mg/d, 4 wk on/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Even small amounts of intravitreally injected VEGF-binding agents were found to alter systemic VEGF-A levels [ 24 – 26 ]. As a consequence, determination of systemic VEGF-A levels is part of the systemic safety analysis in various studies investigating VEGF-binding proteins [ 25 , 27 29 ]. However, due to the use of different protocols in quantifying systemic VEGF-A levels, comparison of the results remains difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Even small amounts of intravitreally injected VEGF-binding agents were found to alter systemic VEGF-A levels [ 24 – 26 ]. As a consequence, determination of systemic VEGF-A levels is part of the systemic safety analysis in various studies investigating VEGF-binding proteins [ 25 , 27 29 ]. However, due to the use of different protocols in quantifying systemic VEGF-A levels, comparison of the results remains difficult.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, another registered TKI directed against VEGFR, sorafenib, combined with bevacizumab did not mention any occurrence of MAHA syndrome nor TMA [ 14 , 16 , 19 ]. Pazopanib combined with bevacizumab might damage the renal nephron, with a rapid onset of a microangiopathy closed to that reported in the combination of bevacizumab with sunitinib [ 28 ]. In addition, our series confirmed that this microangiopathic effect does not only occur in patients suffering from renal tumors.…”
Section: Discussionmentioning
confidence: 79%
“…The combination of the VEGF-directed monoclonal antibody bevacizumab with a tyrosine kinase inhibitor directed against VEGF receptors has already been investigated [ 28 ]. These combination regimens were difficult to manage since increased toxicities have been described, and some of them were even considered as not feasible despite promising efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations